2015
DOI: 10.1039/c5py01175b
|View full text |Cite
|
Sign up to set email alerts
|

Preferential chiral solvation induced supramolecular chirality in optically inactive star Azo polymers: photocontrollability, chiral amplification and topological effects

Abstract: A series of star-shaped azobenzene (Azo)-containing side chain polymers with 3, 4 and 6 arms were synthesized by the atom transfer radical polymerization technique initiated by multifunctional initiators. The intense bisignated circular dichroism (CD) signals in the UV-vis region were observed when these star polymers aggregated in a dichloroethane/limonene mixed solvent, indicating the successful chirality transfer from limonene molecules to these star Azo polymers. The chirality originates from the preferent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

6
3

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 84 publications
0
23
0
Order By: Relevance
“…However, this induction and assembly process of main chain Azo-containing polymers requires a complex system consisting of the good solvent, a chiral solvent, and a weak solvent. Recently, we further simplified the assembled components of a side-chain Azo-containing polymer by using limonene as the weak and chiral solvent simultaneously [27,29,30]. On the one hand, although much effort has been paid to simplifying the assembled components and studying the inducing mechanism, we still have a problem remaining to be solved of whether the construction of supramolecular chirality in the achiral side-chain Azo-containing polymer can be achieved by pure limonene under the controlled temperature.…”
Section: Introductionmentioning
confidence: 99%
“…However, this induction and assembly process of main chain Azo-containing polymers requires a complex system consisting of the good solvent, a chiral solvent, and a weak solvent. Recently, we further simplified the assembled components of a side-chain Azo-containing polymer by using limonene as the weak and chiral solvent simultaneously [27,29,30]. On the one hand, although much effort has been paid to simplifying the assembled components and studying the inducing mechanism, we still have a problem remaining to be solved of whether the construction of supramolecular chirality in the achiral side-chain Azo-containing polymer can be achieved by pure limonene under the controlled temperature.…”
Section: Introductionmentioning
confidence: 99%
“…In this system, chiroptical switching was achieved through the reversible modulation of the supramolecular helicity of Azo building blocks. Subsequently, Zhang and coworkers systematically investigated the effects of spacer lengths, topological structures and push-pull electronic substituents in Azo-polymer 20, on the chiral limonene induced supramolecular chirality [ 133 , 134 , 201 ]. The results of CD and UV-vis spectra suggested that the internal structures and external stimuli have distinctive influences on the induction and regulation of supramolecular chirality of achiral Azo-polymers.…”
Section: Supramolecular Chirality Of Azo-polymers Constructed By Pmentioning
confidence: 99%
“…Meanwhile, many diverse factors, such as tersolvent composition, solvent polarity, polymer molecular weight, alkyl chain length, limonene enantiopurity, solution temperature, clockwise and counter-clockwise stirring, and aggregate size are confirmed to influence the magnitude of the induced CD and/or CPL amplitude. Through theoretical calculation, they assume that the inherent twisting ability (H-H repulsion) between the near- Zhang et al demonstrated that solvent chirality can be transferred to the aggregates of many optically inactive π-conjugated polymers with different backbone structures, such as main chain azo-containing polyfluorene (F8AZO), poly(9,9-di-n-octylfluorenyl-2,7-diyl) (PF8), poly(9,9-di-noctylsila-fluorenyl-2,7-diyl) (PSi8), poly(9-(1-octylnonyl)-9H-carbazole-2,7-diyl) (PCz8), P(F8-alt-Si8), P(F8-alt-Cz8), and P(Si8-alt-Cz8), hyperbranched PF8s, side chain azo-containing polymers PAzoMA, P(AzoMA-rans-MMA), and star side-chain Azo polymers (star PAzoMAs) as shown in Figure 6 [69,[72][73][74][75][76]. Optically active F8AZO aggregates were successfully generated by the chirality transfer from (S)-and (R)-limonene, demonstrated by the intense ICD signals corresponding to F8AZO in the visible region [69].…”
Section: Preparation For Optically Active π-Conjugated Polymermentioning
confidence: 99%
“…However, a more recent study demonstrated that the signs depend essentially only on the nature of the polymer host supramolecular chirality, but not on the R or S solvent chirality, proven by the VCD spectra of the δ-phase s-PS film used [78]. To investigate the induction of supramolecular chirality for achiral side-chain polymers, Zhang et al designed serials of linear and star-shaped achiral side chain azobenzene-containing polymer (PAzoMA, P(AzoMA-rans-MMA), and star PAzoMAs) [75,76]. Chirality of nonracemic solvents were successfully transferred to these polymers, and well-assembled supramolecular transazobenzene aggregates are prepared in DCE/(R)-or (S)-limonene mixsolvents.…”
Section: Preparation For Optically Active π-Conjugated Polymermentioning
confidence: 99%